(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This study focused on The Role of Social media in Preventing Cyber Fraud at Barangay 165 Bagbaguin Caloocan City. The respondents are 40 Residents and 10 Law Enforcement agencies who participated during the data-gathering phase. It focused on the following: 1) Demographic profile of the respondents. 2) Respondents assess the Role of Social media in Preventing Cyber Fraud at Barangay 165 Bagbaguin Caloocan city. In terms of compromise, cyber scams, and information. 3) Problems encountered by the respondents in Barangay 165 Bagbaguin Caloocan city. 4) Measure that may be proposed to address the problems encountered by Barangay 165 Bagbaguin Caloocan city in Preventing Cyber fraud. The statistical tools used were frequency and percentage, weighted mean, ranking, and Likert Scale.